Brackish water Oscillatoriaceae from North 24-Parganas, West Bengal, India - Naskar, Nurmohammad; Naskar, K.R.; Sen, C.R. (Bangladesh Journal of Plant Taxonomy, 2008)
The present communication enumerates 40 taxa of Oscillatoriaceae from the brackish water wetlands of North 24-Parganas district of West Bengal. Out of the reported taxa, 12 are from each of Lyngbya and Oscillatoria, 6 from each of Phormidium and Spirulina, 2 belong to Schizothrix, and Hydrocoleum and Katagnymene are represented by one species each. A close relationship was observed between seasonal water temperature and salinity levels of the wetlands in enhancing algal population. Keywords: Brackish water, species diversity, ecosystem, Oscillatoriaceae, North 24-Parganas, West Bengal DOI: 10.3329/bjpt.v15i1.909 Bangladesh J. Plant Taxon. 15(1): 31-38, 2008 (June)